SIMULASI KENDALi PUTARAN MOTOR DC BERBASIS LOGIKA FUZZI - Manurung, Juaksa (JURNAL PENELITIAN SAINTIKA, 2012)
The research done a simulation of de motor speed control amplifier fieldJuzzi logic-based series are very reliable, which can be proved by the results of thisstudy. Characteristics of de motors studied are the characteristics of the motor open that shows a dead time of 0.1 seconds, time stable around 0.6 seconds and theamplitude response only reached 0.1. Characteristics of the motor closed that showsa dead time covered by 0.1 seconds, time stable around 0.6 seconds, but theamplitude of the response does not reach 0.1. Motor speed control with fuzzy logicbased fuzzi associative memory (FAM) generates the standard characteristics of themotor controlled by the dead time is only 0.04 seconds, but after 2 seconds the response has not reached one, but tlwught to be stable. Based motor speed controlwith the FAM-modified fuzzi logic generates the response characteristics, the deadtime is only 0.004 seconds, reaching an amplitude response without overshoot, andsteady in just 0.06 seconds.